Optimizing the Function of Social Media as Education and Motivating Students to Become Investors in Investment Galleries - Toton Fanshurna; Muhammad Mirza Pratama; Matnin Matnin (Publikasi Indonesia, 2025)
This research is motivated by the lack of information that reaches students about the capital market, so that it has an impact on low interest in investing. This is because the sources of information and educational facilities are still limited, therefore there needs to be a breakthrough by optimizing the role of social media. The purpose of this study was to find out how to optimize social media as a means of information and education about the capital market for students to be interested in becoming investors. This study used a qualitative approach with a descriptive research type. Data obtained by distributing questionnaires electronically. The results of the study concluded that to optimize the function of social media as a means of motivating students to invest, it is necessary to strengthen the types of media most often used by students such as Facebook, WhatsApp, Instagram, Telegram, YouTube, and so on, by means of multi-party collaboration such as the role of lecturers, friends, securities and investment galleries. The main basis for optimization is to understand the driving and inhibiting factors for students to invest.